2020
DOI: 10.1038/s41419-020-03195-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of FAM134B in ER-phagy and diseases

Abstract: FAM134B (also called JK-1, RETREG1), a member of the family with sequence similarity 134, was originally discovered as an oncogene in esophageal squamous cell carcinoma. However, its most famous function is that of an ER-phagy-regulating receptor. Over the decades, the powerful biological functions of FAM134B were gradually revealed. Overwhelming evidence indicates that its dysfunction is related to pathophysiological processes such as neuropathy, viral replication, inflammation, and cancer. This review descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 93 publications
1
28
0
Order By: Relevance
“…While there is a growing body of literature on the physiological and pathological roles of FAM134B (Mo et al , 2020 ), FAM134A and FAM134C are still poorly studied. FAM134A has been associated with mitotic progression (Toyoda et al , 2017 ) and is a target of hsa‐miRNA940 in the regulation of osteogenic differentiation (Hashimoto et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a growing body of literature on the physiological and pathological roles of FAM134B (Mo et al , 2020 ), FAM134A and FAM134C are still poorly studied. FAM134A has been associated with mitotic progression (Toyoda et al , 2017 ) and is a target of hsa‐miRNA940 in the regulation of osteogenic differentiation (Hashimoto et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein has been reported to localize to the ER membrane, specifically to tubules and sheet edges (Khaminets et al, 2015;Mo et al, 2020), and in another study, the protein has been shown to primarily localize to the Golgi apparatus (Kurth et al, 2009). The RHD of FAM134B is required for membrane fragmentation in vitro and ER-phagy in vivo under ER stress (Bhaskara et al, 2019;Jiang et al, 2020;D'Eletto et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…The protein has been reported to localize to the ER membrane, specifically to tubules and sheet edges ( Khaminets et al. , 2015 ; Mo et al. , 2020 ), and in another study, the protein has been shown to primarily localize to the Golgi apparatus ( Kurth et al.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, they cannot bind LC3/GABARAP family members or mediate ER-phagy. In this case, impaired ER-phagy flux may contribute to the pathogenesis of HSAN II [ 85 , 86 , 87 , 88 ]. However, other mutations identified from HSAN II patients, such as c.646 G > A (p.G216R), may make FAM134B overactive, thus inducing excessive ER-phagy.…”
Section: The Diseases Relevance Of Er-phagymentioning
confidence: 99%